Rare case report - Recurrent Spindle Cell tumor of the thigh - Mishra, D R Ankur (Indian Journal of Case Reports, 2024)
This case is to discuss the rarest of a rare recurrent spindle cell tumor of the proximal thigh which is one of the soft tissue neoplasms that can occur in various locations of our body including the trunk and extremities. Soft tissue masses are commonly present in surgical practices and range from benign lipomas to high-grade soft tissue sarcomas. A subset of soft tissue sarcomas includes a spindle cell sarcoma, which is a rare connective tissue tumor that originates in the layers of tissue found below the skin. The aim of this case report is to describe the presentation of spindle cell tumors, the investigations required, and the optimal management of the disease. Surgical resection i.e., wide local excision is the mainstay of treatment for spindle cell sarcomas but treatment can also include a combination of surgery, chemotherapy, and radiation.